A sodium ion battery alloy negative electrode material, electrode and preparation method and application thereof

By using PbxBiySnz alloy material and specific preparation methods, the performance problems caused by volume changes in the sodium ion battery negative electrode material during the deintercalation process are solved, and high capacity, long cycle stability and low cost electrochemical performance improvements are achieved.

CN117758129BActive Publication Date: 2025-01-03HEBEI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311573673.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2025-01-03
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

The volume of the existing sodium ion battery negative electrode material changes greatly during the de-embedding process, resulting in powdering and shedding, affecting electrochemical performance, and is costly, making it difficult to take into account the specific capacity, circulation performance and energy density.

Method used

PbxBiySnz (x+y+z=100) alloy negative electrode material is used to form liquid or powder alloy electrodes through specific preparation methods, and the synergistic effect of multi-alloys is used to alleviate volume changes, improve electron and ion conduction, and reduce voltage drop.

Benefits of technology

The negative electrode material of sodium ion battery with high capacity, long cycle stability and low cost is achieved, which improves electrochemical performance and rate performance, avoids powdering and cracking, and enhances conductivity and reactivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117758129B_ABST
    Figure CN117758129B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries and provides a sodium ion battery alloy negative electrode material, an electrode and its application in a sodium ion battery. The composition of the sodium ion battery alloy negative electrode material is Pb x Bi y Sn z , where x+y+z=100, x, y, z<100, is prepared by mixing pure Pb block, Sn block or Bi block according to the target ratio and heating and melting in a smelting furnace. The obtained liquid alloy negative electrode material can be directly coated on the current collector to obtain an alloy electrode, or the powdered alloy, conductive agent and binder are evenly coated on the current collector to obtain an alloy electrode. The alloy negative electrode material of the present invention not only has a simple preparation method and low raw material cost, but also the various metals cooperate with each other to effectively improve the electrochemical activity, reduce the overpotential, and improve the electrode reaction kinetics. It is applied to sodium ion batteries to exert a higher specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery alloy negative electrode material, an electrode, and a preparation method and application thereof. Background Art

[0002] Non-renewable energy sources such as oil, coal, and natural gas are not only facing the risk of increasing depletion, but their over-exploitation and utilization have also brought unprecedented serious environmental problems such as air pollution; while renewable clean energy sources such as wind power, solar power, and hydropower have the defects of intermittent and low conversion efficiency. Therefore, green and efficient electrochemical energy storage technology is favored by today's society. Lithium-ion batteries are widely used in various large-scale products and even in large-scale energy storage grids due to their high voltage platform and stable cycle life. However, the cost problem caused by the low reserves and uneven distribution of lithium resources seriously restricts the development of lithium-ion batteries.

[0003] Sodium ions are considered to be an ideal choice for the next generation of large-scale energy storage technology because they have the same physical and chemical properties as lithium ions and have the advantages of abundant reserves and low prices. Looking at the development history of sodium-ion batteries, we can find that the development of positive electrode materials for sodium-ion batteries is accompanied by breakthroughs in positive electrode materials for lithium-ion batteries. Some positive electrode materials used in lithium-ion batteries can also exhibit good electrochemical properties for sodium storage, such as layered transition metal oxides, polyanionic positive electrodes, etc. However, the negative electrode materials used in lithium-ion batteries have their limitations when used for sodium storage. For example, graphite can only exert about 35 mAh g in the ester electrolyte of sodium battery due to its small interlayer spacing (3.35 Å). -1 The capacity of the hard carbon anode is ~300 mAh g -1 The capacity of sodium-ion batteries is high, but the preparation process is energy-intensive and polluting, which restricts the future development of higher energy density negative electrode materials and large-scale energy storage of sodium-ion batteries. Therefore, the search for high-capacity, long-life, and high-rate negative electrode materials for sodium-ion batteries should receive more attention.

[0004] The negative electrode materials of sodium ion batteries mainly include embedded negative electrode materials, alloy negative electrode materials, conversion negative electrode materials and organic negative electrode materials. Among them, alloy materials have a multi-electron alloying sodium insertion reaction and a low sodium insertion potential (<0.8 V vs. Na + / Na) and a high theoretical specific capacity (>400 mAh g -1 ) is considered to be the most promising negative electrode material. However, this type of material has a serious problem when used as a negative electrode material for sodium-ion batteries, that is, during the process of sodium insertion and extraction, a drastic volume change will occur, which will cause the active material to pulverize and fall off, resulting in poor electrochemical performance. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium ion battery alloy negative electrode material, an electrode and a preparation method and application thereof, aiming to solve the technical problem that the existing sodium ion battery negative electrode materials cannot take into account specific capacity, cycle performance, energy density and cost at the same time.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A sodium ion battery alloy negative electrode material, the composition of the alloy negative electrode material is Pb x Bi y Sn z (wt%), where, x+y+z=100, x, y, z<100.

[0008] Preferably, the alloy negative electrode material includes the following components in weight percentage: Pb: 14.8-44.5wt%, Bi: 16-59.4wt%, Sn: 0-25.8wt%.

[0009] More preferably, the alloy negative electrode material is Pb 32 Bi 52.5 Sn 15.5 (wt%), Pb 28 Bi 50 Sn 22 (wt%), Pb 14.8 Bi 59.4 Sn 25.8 (wt%), Pb 36 Bi 16 Sn 48 (wt%) or Pb 44.5 Bi 55.5 (wt%).

[0010] The method for preparing the above-mentioned sodium ion battery alloy negative electrode material comprises the following steps:

[0011] According to the target ratio, pure Pb, pure Bi or pure Sn with a purity greater than 99.9% is weighed, placed in a crucible and heated in a smelting furnace for smelting. During the smelting process, an inert gas (Ar or N 2 ) protect the liquid surface, and after all the metals are melted, stir them thoroughly to obtain liquid alloy negative electrode material; cast the liquid alloy negative electrode material into a mold, and store it in the form of an alloy ingot after cooling and solidification; the alloy ingot is heated and melted to form a liquid alloy negative electrode material again, or it can be heated and melted, dispersed in liquid state, and dried to obtain a powdered alloy negative electrode material.

[0012] The present invention also provides application of the above-mentioned sodium ion battery alloy negative electrode material in sodium ion battery electrodes.

[0013] A sodium ion battery alloy electrode is prepared by the following two methods (such as Figure 1 shown):

[0014] (1) The liquid alloy is uniformly coated on the current collector, and after cooling and solidification, an integrated alloy electrode for a sodium ion battery is obtained.

[0015] The liquid alloy is prepared by the above-mentioned method for preparing the liquid alloy negative electrode material.

[0016] Specifically, the method for preparing an integrated alloy electrode for a sodium ion battery using liquid alloy is as follows:

[0017] Cut a 10 cm × 10 cm piece of aluminum foil, wipe the rough surface repeatedly with alcohol to remove oil stains and dust on the surface, and use it as a current collector; wipe the heating table with alcohol, weigh a certain mass of alloy ingots and melt them on the aluminum foil on the heating table, and evenly scrape the molten alloy ingot (i.e., liquid alloy) on the aluminum foil with a scalpel, paying attention to removing the debris and oxides on the surface; finally, place the aluminum foil evenly covered with the alloy in a cool place and cool and solidify naturally to obtain integrated alloy electrode sheets for sodium ion batteries with different loadings.

[0018] Preferably, the current collector is one of copper foil, aluminum foil or stainless steel; more preferably aluminum foil.

[0019] No conductive agent is added in the preparation of the integrated alloy electrode for the sodium ion battery, which reduces the loss of irreversible capacity and enables the alloy electrode material to better exert the electrochemical properties of the three metals, with better electrochemical activity, good capacity retention rate, and higher energy utilization and coulombic efficiency.

[0020] (2) The powdered alloy, conductive agent and binder are uniformly mixed under the action of a solvent, uniformly coated on a current collector, and dried to obtain a sodium ion battery powder alloy electrode.

[0021] The powder alloy is prepared by adopting the method for preparing the powder alloy negative electrode material.

[0022] Specifically, the method for preparing a sodium ion battery alloy electrode using a powdered alloy is as follows:

[0023] ① Take 1g alloy ingot, 30ml liquid paraffin and 0.1g sodium stearate and place them in a 100mL three-necked flask with a magnet. Block the other two necks of the three-necked flask with stoppers, pass argon for about half an hour to remove the oxygen in it, then seal it and place it on a heating stirrer, heat it to the melting point of the alloy and keep stirring at that temperature for 8 hours, then remove the heat source, cool it to room temperature, take the remaining precipitate, wash it with chloroform centrifugation and filter it three times, and finally dry the obtained sample in a vacuum oven at 65℃ for 8 hours to obtain alloy powder;

[0024] ② The above powdered alloy, Super P and CMC binder were uniformly mixed in a mass ratio of 8:1:1, dispersed in deionized water, ground evenly to make a slurry, and then coated on the current collector with a scraper. It was placed in a vacuum oven at 70°C and dried for 12 h to obtain a sodium ion battery powder alloy electrode. The dried alloy electrode was cut into small discs with a diameter of 12 mm. After the electrode sheets were numbered and weighed, they were placed in a glove box for standby use.

[0025] Preferably, the mass ratio of the powdered alloy, the conductive agent and the binder is 8:1:1.

[0026] Preferably, the current collector is one of copper foil, aluminum foil or stainless steel; more preferably aluminum foil.

[0027] Preferably, the conductive agent is one of conductive carbon black, Super P, Ketjen black, acetylene black, activated carbon, porous carbon or natural graphite; more preferably Super P.

[0028] Preferably, the binder is one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), sodium alginate, polytetrafluoroethylene, and polyacrylic acid (PAA); more preferably CMC.

[0029] Preferably, the solvent is N-methylpyrrolidone (NMP) or deionized water.

[0030] A sodium ion battery alloy electrode is prepared by the preparation method of the sodium ion battery integrated alloy electrode or powder alloy electrode described in the present invention.

[0031] A sodium ion battery, comprising the sodium ion battery alloy electrode of the present invention.

[0032] Specifically, a high-capacity multi-gradient sodium ion half-cell comprises the sodium ion battery alloy electrode, sodium foil, diaphragm and electrolyte described in the present invention; the sodium foil is an electrode made of metallic sodium, and the electrolyte has a soluble sodium salt as a solute and an organic reagent as a solvent. The preparation method thereof is as follows:

[0033] In O 2 <0.01 ppm, H 2 In a glove box with O<0.01 ppm, the negative electrode shell, sodium foil, diaphragm, electrolyte, sodium ion battery alloy electrode, gasket, shrapnel, and positive electrode shell are stacked in this order, and 60 μL of electrolyte is dripped on the diaphragm to make it completely soaked, and the battery is encapsulated to obtain a button battery.

[0034] Preferably, the soluble sodium salt is one of sodium perchlorate, sodium hexafluorophosphate or sodium trifluoromethanesulfonate.

[0035] Preferably, the organic reagent is one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether or tetraethylene glycol dimethyl ether.

[0036] Preferably, the diaphragm is permeable to sodium ions and ensures that the sodium ions can be transmitted freely, and can be glass fiber filter paper, polyolefin composite diaphragm or organic polymer non-woven fabric.

[0037] Preferably, the diameter of the sodium foil is 12 μm.

[0038] More preferably, the soluble sodium salt is sodium hexafluorophosphate, the organic reagent is diethylene glycol dimethyl ether, the electrolyte concentration is 1 mol / L, and the separator is glass fiber.

[0039] The sodium ion battery alloy negative electrode material described in the present invention is composed of a binary or ternary alloy of at least two of the metals Pb, Bi or Sn. The theoretical capacity of a single Bi metal is lower than that of other alloy negative electrodes, which is not conducive to the construction of a high energy density negative electrode material. The volume expansion of a single Sn metal is as high as 420%, which will cause serious pulverization of the electrode material, and there is a certain voltage surge in each phase change process, which greatly affects the cycle stability of the material. The present invention prepares metal Pb, Bi or Sn into an alloy material through a specific preparation method, which effectively alleviates the defects of using the above materials alone. The multi-element alloys have a synergistic effect, effectively promote the conduction of electrons and ions, and improve the overall electrochemical performance. By introducing Bi with a smaller volume change, the expansion of Sn with a larger volume change is effectively alleviated, and the sodium insertion reaction step is added to slow down the effect of the volume expansion of the metal on the structure during the reaction. At the same time, the Na first generated at a high potential during the discharge process 3 Bi alloy improves the rapid sodium ion diffusion channel for the subsequent sodium insertion reaction, and the introduction of low-cost Pb can alleviate problems such as voltage drop, making the charge and discharge platform smoother, giving full play to the synergistic effect between metals, and improving long-cycle stability and rate performance.

[0040] Beneficial effects:

[0041] The present invention provides a high-capacity multi-gradient potential sodium-intercalation alloy negative electrode material, electrode, preparation method thereof and application in sodium ion batteries. The alloy negative electrode material is prepared by a specific preparation method, which is not only simple in preparation method and low in raw material cost, but also gives full play to the synergistic effect between the metals: the three metals are located in the same system and cross-linked with each other, and influence each other. They can support each other during the charging and discharging process. During the sodium storage process, the unreacted metal can act as a buffer "collective" to alleviate volume expansion, while enhancing conductivity and maintaining the integrity of the electrode morphology; the reacted metal after sodium intercalation can provide a fast ion diffusion channel for the subsequent metal reaction, ensuring rapid kinetic behavior, thereby jointly improving the overall electrochemical performance of the electrode. In the process of sodium ion deintercalation, the alloy material generates less internal stress than a single bulk metal as an alloy negative electrode, which controls the cracking and pulverization of the alloy to a certain extent, and is conducive to improving the stability of the particles, so that the electrode has better rate performance and long cycle performance.

[0042] In addition, the alloy negative electrode material of the present invention has a high reactivity, and its alloying and dealloying processes are highly reversible, avoiding the pre-sodiumization process, and alleviating the problems of low coulombic efficiency and poor reversibility of the traditional alloyed negative electrode. The embodiment shows that its first-cycle coulombic efficiency is higher than that of most reported alloyed negative electrodes and binary / ternary alloy negative electrodes. The electrode prepared from the alloy material of the present invention can exert a higher specific capacity than the electrode prepared by directly mixing Pb powder, Bi powder and Sn powder in the same proportion, and has more excellent rate performance, cycle stability and electrochemical activity. The present invention provides a new idea for constructing negative electrode materials with high energy density, long cycle life and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic diagram of the preparation method of powder alloy electrode and integrated alloy electrode.

[0044] Figure 2 Example 1 Pb 32 Bi 52.5 Sn 15.5 (wt%) XRD pattern of ternary alloy powder.

[0045] Figure 3 Example 1 Pb 32 Bi 52.5 Sn 15.5 (wt%) SEM image of ternary alloy powder.

[0046] Figure 4 Example 2 Pb 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from the ternary alloy powder (wt%) has a high conductivity at 0.1 mV s-1 Cyclic voltammetry curves at a scan rate of .

[0047] Figure 5 Example 2 Pb 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from the ternary alloy powder (wt%) at 50 mA g -1 Charge and discharge curves at current density.

[0048] Figure 6 Example 2 Pb 32 Bi 52.5 Sn 15.5 Rate performance diagram of sodium ion half-cell assembled with (wt%) ternary alloy powder at different current densities.

[0049] Figure 7 Example 2 Pb 32 Bi 52.5 Sn 15.5 (wt%) sodium ion half-cell assembled from ternary alloy powders at 1 Ag -1 Cycling performance diagram at current density of .

[0050] Figure 8 Example 3 Pb 32 Bi 52.5 Sn 15.5 The integrated electrode prepared by ternary alloy solution (wt%) was -1 Charge and discharge curves at current density.

[0051] Fig. 9 Example 3 Pb 32 Bi 52.5 Sn 15.5 The integrated electrode prepared by ternary alloy solution (wt%) was -1 Cycling performance diagram at current density of .

[0052] Fig.10 Comparative Example 1 Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder with Pb 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from the ternary alloy powder (wt%) was tested at 100 mA g -1 Comparison of charge and discharge curves at current density.

[0053] Fig.11 Comparative Example 1 Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder with Pb 32 Bi 52.5 Sn 15.5 Comparison of the rate performance of sodium-ion half-cells assembled from (wt%) ternary alloy powders at different current densities.

[0054] Fig.12 Comparative Example 1 Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder with Pb 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from ternary alloy powders (wt%) at 1 A g -1 Comparison of cycling performance at current density.

[0055] Fig.13 Example 4 Pb 28 Bi 50 Sn 22 (wt%) sodium ion half-cell assembled from ternary alloy powder at 50 mAg -1 Charge and discharge curves at current density.

[0056] Fig.14 Example 4 Pb 28 Bi 50 Sn 22 The sodium ion half-cell assembled from ternary alloy powders (wt%) at 1 A g -1 Cycling performance diagram at current density of .

[0057] Fig.15 Example 5 Pb 14.8 Bi 59.4 Sn 25.8 The sodium ion half-cell assembled from the ternary alloy powder (wt%) at 50 mA g -1 Charge and discharge curves at current density.

[0058] Fig.16 Example 5 Pb 14.8 Bi 59.4 Sn 25.8 The sodium ion half-cell assembled from ternary alloy powder (wt%) at 1A g -1 Cycling performance diagram at current density of .

[0059] Fig.17 Example 6 Pb 36 Bi 16 Sn 48 (wt%) sodium ion half-cell assembled from ternary alloy powder at 50 mAg-1 Charge and discharge curves at current density.

[0060] Fig.18 Example 6 Pb 36 Bi 16 Sn 48 The sodium ion half-cell assembled from ternary alloy powders (wt%) at 1 A g -1 Cycling performance diagram at current density of .

[0061] Fig.19 Example 7 Pb 44.5 Bi 55.5 (wt%) XRD patterns of binary alloy powders.

[0062] Fig. 20 Example 7 Pb 44.5 Bi 55.5 (wt%) SEM image of binary alloy powder.

[0063] Fig.21 Example 7 Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) has a peak current of 0.1 mVs -1 Cyclic voltammetry curves at a scan rate of .

[0064] Fig. 22 Example 7 Pb 44.5 Bi 55.5 (wt%) binary alloy powders assembled into a sodium ion half-cell at 50 mAg -1 Charge and discharge curves at current density.

[0065] Fig.23 Example 7 Pb 44.5 Bi 55.5 Rate performance diagram of sodium ion half-cell assembled with (wt%) binary alloy powder at different current densities.

[0066] Fig.24 Example 7 Pb 44.5 Bi 55.5 Sodium ion half-cell assembled from binary alloy powders (wt%) at 1 A g -1 Cycling performance diagram at current density of .

[0067] Fig.25 Comparative Example 2 Pb 44.5 / Bi 55.5 Mixed powder with Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) at 50 mA g-1 Comparison of charge and discharge curves under different current densities.

[0068] Fig.26 Comparative Example 2 Pb 44.5 / Bi 55.5 Mixed powder with Pb 44.5 Bi 55.5 Comparison of the rate performance of sodium-ion half-cells assembled from (wt%) binary alloy powders at different current densities.

[0069] Fig. 27 Comparative Example 2 Pb 44.5 / Bi 55.5 Mixed powder with Pb 44.5 Bi 55.5 Sodium ion half-cell assembled from binary alloy powders (wt%) at 1 A g -1 Comparison of cycling performance at current density.

[0070] Fig.28 Example 8 NVPF / / Pb 32 Bi 52.5 Sn 15.5 Schematic diagram of the working principle of the full battery.

[0071] Fig.29 Example 8 NVPF / / Pb 32 Bi 52.5 Sn 15.5 The full cell was tested at a current density of 50 mA g -1 The charge and discharge curve diagram below.

[0072] Fig.30 Example 8 NVPF / / Pb 32 Bi 52.5 Sn 15.5 The full cell was charged at a current density of 1000 mA g -1 The cycle performance diagram below. DETAILED DESCRIPTION

[0073] The present invention is further described below in conjunction with embodiments, but the scope of the present invention is not limited thereto, and any changes based on the present invention are within the protection scope of the present invention.

[0074] The processes and methods not described in detail in the following examples are conventional methods known in the art, and the reagents used in the examples are all analytically pure or battery grade, and can be purchased commercially or prepared by methods well known to those skilled in the art. The following examples all achieve the purpose of the present invention.

[0075] Example 1

[0076] This embodiment provides a high-capacity alloy negative electrode material: Pb 32 Bi 52.5 Sn 15.5 (wt%) ternary alloy material, the specific synthesis method is as follows:

[0077] (1) The purity of the metal materials used in the present invention is higher than 99.99% and can be used without further purification. The mass percentage of the required metals is: Pb: 32%, Bi: 52.5%, Sn: 15.5%. Pb blocks, Bi blocks and Sn blocks are weighed according to the target ratio, mixed and placed in a ceramic crucible, heated in a smelting furnace, and fully stirred after all the metals are melted to obtain an alloy solution;

[0078] (2) Casting the refined alloy liquid into a customized mold to form an alloy ingot;

[0079] (3) Take 1g alloy ingot, 30ml liquid paraffin and 0.1g sodium stearate and place them in a 100mL three-necked flask with a magnet. The other two necks of the three-necked flask are plugged with stoppers. Argon is introduced for about half an hour to remove the oxygen in it. Then it is sealed and placed on a heating stirrer. After heating to 100℃ and stirring at this temperature for 8 hours, the heat source is removed and cooled to room temperature. The final precipitate is washed and filtered three times by centrifugation with chloroform. Finally, the obtained sample is placed in a vacuum oven at 65℃ and dried for 8 hours to obtain Pb 32 Bi 52.5 Sn 15.5 (wt%) ternary alloy powder.

[0080] Figure 2 Pb 32 Bi 52.5 Sn 15.5 The X-ray diffraction results of the ternary alloy powder show that the alloy material is composed of hexagonal Pb 7 Bi 3 , tetragonal Sn and rhombohedral Bi. The scanning electron microscope image of the alloy powder is as follows Figure 3 As shown, it can be seen that the alloy material is in a regular spherical shape, and the particle size is mainly distributed around 15 μm.

[0081] Example 2

[0082] The Pb prepared in Example 1 32 Bi 52.5 Sn 15.5 (wt%) ternary alloy powder was prepared into electrode sheets and assembled into sodium ion half-cells for electrochemical performance testing. The specific method is as follows:

[0083] Pb 32 Bi52.5 Sn 15.5 The alloy powder, Super P and CMC binder were uniformly mixed in a mass ratio of 8:1:1, dispersed in deionized water, ground evenly to make a slurry, and then scraped evenly with a 100 μm scraper and dried in a vacuum oven at 70 °C for 10 h to obtain Pb 32 Bi 52.5 Sn 15.5 The ternary alloy electrode is dried Pb 32 Bi 52.5 Sn 15.5 The electrodes were cut into small discs with a diameter of 12 mm. After being numbered and weighed, the electrode discs were placed in a glove box for later use.

[0084] The prepared electrode sheet was used as the working electrode, pure sodium foil was used as the counter electrode, 2 layers of glass fiber and 1 layer of celgard were used as the separator, and 1M NaPF 6 / diethylene glycol dimethyl ether solution as the electrolyte, in O 2 <0.01 ppm, H 2 The cells were assembled into button cells in a glove box with O < 0.01 ppm.

[0085] The battery prepared in this example was subjected to cyclic voltammetry test using a CHI760E electrochemical workstation, with a voltage range of 0.01-1.2 V. The battery performance test was performed using a blue battery test system: constant current charge and discharge, rate performance, and long cycle tests were performed at room temperature with a voltage range of 0.01-1.2 V.

[0086] Figure 4 The scan rate is 0.1 mVs -1 Next, Pb 32 Bi 52.5 Sn 15.5 The first three cycles of the sodium ion half-cell assembled from the (wt%) ternary alloy material are shown in the cyclic voltammetry curve. Five reduction peaks and eight oxidation peaks can be observed from the figure, corresponding to the alloying and dealloying processes of the three metals. At the same time, it can be seen that the first three cycles of the curves have good overlap, further indicating that the alloying and dealloying processes of the alloy material of the present invention are highly reversible.

[0087] Figure 5 The current density is 50 mA g -1 Next, Pb 32 Bi 52.5 Sn 15.5 The first three charge-discharge curves of the sodium ion half-cell assembled from the ternary alloy powder (wt%). It can be seen that the charge-discharge curve is consistent with the cyclic voltammetry curve. The first charge-discharge curve shows that its initial discharge capacity is 549.6 mAh g -1, charging capacity is 520 mAhg -1 , the first-cycle coulombic efficiency is as high as 94.6%. It is worth noting that the first-cycle coulombic efficiency of this material is higher than that of most reported alloyed negative electrodes and binary / ternary alloy negative electrodes, indicating that this material has high reactivity and reversibility, avoiding the pre-sodiumization process and alleviating the problems of low coulombic efficiency and poor reversibility of traditional alloyed negative electrodes.

[0088] Figure 6 Pb 32 Bi 52.5 Sn 15.5 (wt%) sodium ion half-cell assembled from ternary alloy powder at different current densities. The current densities are 50, 100, 200, 500, 800, 1000, 2000, 3000, 5000, and 8000 mAg -1 The rate performance test was carried out under the condition of 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from ternary alloy materials (wt%) has a good performance even at 8000 mA g -1 At high current density, 170 mAh g -1 capacity, and returns to 50mAg -1 After the current density reaches 10000, the specific capacity still has almost no decay. This shows that the alloy material of the present invention has excellent cycle stability, the reaction of the alloy electrode in the process of sodium ion insertion and extraction is reversible, and the structure is stable.

[0089] Figure 7 Pb 32 Bi 52.5 Sn 15.5 (wt%) sodium ion half-cell assembled from ternary alloy powder at 1000mAg -1 Cyclic stability test results under current density. It can be seen that after 500 cycles, Pb 32 Bi 52.5 Sn 15.5 The capacity retention rate of the sodium ion half-cell assembled from the (wt%) ternary alloy material is still as high as 95%, and the coulombic efficiency per cycle is ~100%. This further demonstrates that the alloy material has excellent cycle stability and electrochemical performance.

[0090] Example 3

[0091] Pb 32 Bi 52.5 Sn 15.5 (wt%) ternary alloy liquid was prepared into Pb 32 Bi 52.5 Sn 15.5(wt%) ternary integrated alloy electrode:

[0092] Cut a piece of aluminum foil of 10 cm × 10 cm, wipe the rough surface with alcohol repeatedly to remove the oil stains and dust on the surface, and use it as a current collector; wipe the heating table with alcohol, weigh the Pb 32 Bi 52.5 Sn 15.5 A total of 0.5 g (wt%) of ternary alloy ingots were melted directly on the aluminum foil on the heating table. The molten alloy ingots were evenly scraped on the aluminum foil with a scalpel, and the surface debris oxides were removed. Finally, the aluminum foil evenly covered with alloy was placed in a cool place to cool naturally, and the electrode sheets with different loadings were obtained. The small discs with a diameter of 12 mm were cut with a cutting machine and set aside.

[0093] The preparation of the electrode does not require the addition of a conductive agent and carbon black. Subsequently, it is assembled into a sodium ion half-cell for electrochemical performance testing. The specific testing method is the same as above.

[0094] Figure 8 The current density is 100 mA g -1 Next, Pb 32 Bi 52.5 Sn 15.5 The charge-discharge curves of the first three cycles of the electrode prepared by directly coating the ternary alloy liquid on the current collector. From the first cycle charge-discharge curve, it can be seen that its initial discharge capacity is 491.27 mAh g -1 , the charging capacity is 474.44mAhg -1 , the first-cycle coulombic efficiency is as high as 96.57%. Similarly, the first-cycle coulombic efficiency of this material is higher than that of most reported alloyed negative electrodes and ternary alloy negative electrodes, further indicating that the alloy material has high reactivity and reversibility. In addition, the addition of non-conductive carbon also reduces the loss of irreversible capacity, resulting in a higher first-cycle coulombic efficiency.

[0095] Fig. 9 The current density is 100 mA g -1 At a current density of 32 Bi 52.5 Sn 15.5 Long cycle test diagram of the electrode prepared by directly coating the (wt%) ternary alloy liquid on the current collector. After 80 cycles, the electrode can still play 447.6mAhg -1 The capacity and coulombic efficiency are close to 100%, indicating that the alloy electrode material has good stability and reversibility.

[0096] Comparative Example 1

[0097] The Pb in Example 2 32 Bi52.5 Sn 15.5 The ternary alloy powder is replaced with a mixture of Pb, Bi, and Sn powders in the same proportion as the negative electrode material of the sodium ion battery, and the rest remains unchanged, which is recorded as Pb 32 / Bi 52.5 / Sn 15.5 The powders were mixed and then assembled into sodium ion half-cells for electrochemical performance testing. The specific method is as follows:

[0098] When preparing the electrode, if the Pb in Example 2 32 Bi 52.5 Sn 15.5 (wt%) ternary alloy powder, i.e., active material, weighed 80 mg. Similarly, the active material Pb in this comparative example 32 / Bi 52.5 / Sn 15.5 The mixed powder is also weighed 80 mg, then the corresponding Pb powder is weighed (according to Pb 32 Bi 52.5 Sn 15.5 The mass of the powder (calculated by mass fraction) is 25.6 mg, the mass of the Bi powder is 42 mg, and the mass of the Sn powder is 12.4 mg. After the mixed powder is prepared, the Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder electrodes and half cells.

[0099] The battery performance test was carried out using the Blue Electric Battery Test System: constant current charge and discharge, rate and long cycle tests were carried out at room temperature in the voltage range of 0.01-1.2 V. The test results were similar to those of Pb 32 Bi 52.5 Sn 15.5 The comparison results of ternary alloy electrodes are as follows.

[0100] Fig.10 Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder with Pb 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from the ternary alloy powder (wt%) was tested at 100 mA g -1 Comparison of charge and discharge curves at different current densities. 32 Bi 52.5 Sn 15.5 The ternary alloy electrode has a slower charge and discharge platform and smaller polarization, which effectively alleviates the voltage drop problem. After charging and discharging the two electrodes, it can be found that Pb 32 Bi52.5 Sn 15.5 The ternary alloy electrode has greater energy utilization and coulombic efficiency. 32 Bi 52.5 Sn 15.5 Ternary alloy materials can better exert the electrochemical properties of three metals and have better electrochemical activity.

[0101] Fig.11 Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder with Pb 32 Bi 52.5 Sn 15.5 (wt%) comparison of the rate performance of sodium ion half-cells assembled from ternary alloy powders at different current densities. -1 The rate performance test was carried out at a current density of 8 Ag. -1 At a current density of 32 Bi 52.5 Sn 15.5 The electrode prepared by the ternary alloy material can still obtain 170 mAhg -1 The capacity of Pb 32 / Bi 52.5 / Sn 15.5 The electrode prepared by mixed powder is 8 Ag -1 At a current density of only 60 mAhg -1 The capacity of Pb 32 Bi 52.5 Sn 15.5 Ternary alloy materials have excellent rate performance.

[0102] Fig.12 Pb 32 / Bi 52.5 / Sn 15.5 Mixed powder with Pb 32 Bi 52.5 Sn 15.5 The sodium ion half-cell assembled from ternary alloy powders (wt%) at 1 A g -1 Comparison of cycling stability at current density. As can be seen from the figure, Pb 32 Bi 52.5 Sn 15.5 The electrode prepared by the ternary alloy material can still obtain 468.5 mAh g after 500 cycles. -1The capacity retention rate is as high as 95%, indicating that the material has excellent long-term cycle stability. 32 / Bi 52.5 / Sn 15.5 After 500 cycles of the electrode prepared by the mixed powder, the capacity retention rate was only 64.85%. 32 Bi 52.5 Sn 15.5 The ternary alloy material has excellent long cycle performance. This is because the ternary alloy material has smaller stress during the sodium insertion and deinsertion process than a single metal mixture. The cracking and pulverization of the alloy are controlled to a certain extent. The ternary alloy electrode prepared in this way has more stable cycle performance and exhibits excellent electrochemical properties.

[0103] Example 4

[0104] This embodiment provides a high-capacity alloy negative electrode material: Pb 28 Bi 50 Sn 22 (wt%) ternary alloy material.

[0105] First, prepare Pb 28 Bi 50 Sn 22 (wt%) ternary alloy powder, except for the mass percentage of the metal required for the alloy and the heating temperature on the heating stirrer being 110°C, the remaining steps are consistent with Example 1. Then, Pb 28 Bi 50 Sn 22 (wt%) ternary alloy electrodes were assembled into sodium ion half-cells for electrochemical performance testing.

[0106] The battery prepared in this example was subjected to battery performance testing using a blue battery testing system: constant current charge and discharge and long cycle testing were performed at room temperature in a voltage range of 0.01-1.2 V.

[0107] Fig.13 Pb 28 Bi 50 Sn 22 The sodium ion half-cell assembled from the ternary alloy powder (wt%) at 50 mA g -1 The first three cycles of charge and discharge curves at a current density of . From the first cycle of charge and discharge curve, we can see that its initial discharge capacity is 591.24mAhg -1 , the charging capacity is 541.46mAhg -1 The first cycle Coulomb efficiency is as high as 91.6%. The highly overlapping charge and discharge curves show that the Pb 28 Bi 50 Sn22 The alloying and dealloying processes of ternary alloy materials are highly reversible.

[0108] Fig.14 Pb 28 Bi 50 Sn 22 (wt%) sodium ion half-cell assembled from ternary alloy powder at 1000mAg -1 The cycle stability test results under current density. It can be seen that after 500 cycles, it can still obtain 464.5mAhg -1 The capacity retention rate is as high as 97%, and the coulombic efficiency per cycle is ~100%. This shows that the alloy material has excellent cycle stability and electrochemical performance.

[0109] Example 5

[0110] This embodiment provides a high-capacity alloy negative electrode material: Pb 14.8 Bi 59.4 Sn 25.8 (wt%) ternary alloy material.

[0111] First, prepare Pb 14.8 Bi 59.4 Sn 25.8 (wt%) ternary alloy powder, except for the mass percentage of the metal required for the alloy and the heating temperature on the heating stirrer being 120°C, the remaining steps are the same as in Example 1. Then, Pb 14.8 Bi 59.4 Sn 25.8 (wt%) ternary alloy electrodes were assembled into sodium ion half-cells for electrochemical performance testing.

[0112] Fig.15 Pb 14.8 Bi 59.4 Sn 25.8 The charge and discharge curves of the first three cycles of the sodium ion half-cell assembled from the ternary alloy powder (wt%). From the first cycle charge and discharge curve, we can see that its initial discharge capacity is 590.82 mAh g -1 , the charging capacity is 555.39 mAhg -1 The first cycle Coulombic efficiency is as high as 94.0%. The highly overlapping charge and discharge curves show that the Pb 14.8 Bi 59.4 Sn 25.8 (wt%) The alloying and dealloying processes of ternary alloy materials are highly reversible.

[0113] Fig.16 Pb 14.8 Bi 59.4 Sn 25.8The sodium ion half-cell assembled from the ternary alloy powder (wt%) was tested at 1000 mA g -1 The cycle stability test results under current density. It can be seen that after 500 cycles, it can still obtain 468.0 mAhg -1 The capacity retention rate is as high as 91.43%, and the coulombic efficiency per cycle is ~100%. 14.8 Bi 59.4 Sn 25.8 (wt%) ternary alloy materials have excellent cycling stability and electrochemical performance.

[0114] Example 6

[0115] This embodiment provides a high-capacity alloy negative electrode material: Pb 36 Bi 16 Sn 48 (wt%) ternary alloy material.

[0116] First, prepare Pb 36 Bi 16 Sn 48 (wt%) ternary alloy powder, except for the mass percentage of the metal required for the alloy and the heating temperature on the heating stirrer being 170°C, the remaining steps are the same as in Example 1. Then, Pb 36 Bi 16 Sn 48 (wt%) ternary alloy electrodes were assembled into sodium ion half-cells for electrochemical performance testing.

[0117] Fig.17 The current density is 50 mA g -1 Next Pb 36 Bi 16 Sn 48 The charge and discharge curves of the first three cycles of the sodium ion half-cell assembled from the ternary alloy powder (wt%). From the first cycle charge and discharge curve, we can see that its initial discharge capacity is 729.8 mAh g -1 , charging capacity is 635.2mAhg -1 The first cycle Coulomb efficiency is 87.0%. The highly overlapped charge and discharge curves show that the Pb 28 Bi 50 Sn 22 The alloying and dealloying processes are highly reversible.

[0118] Fig.18 Pb 36 Bi 16 Sn 48 The sodium ion half-cell assembled from the ternary alloy powder (wt%) was tested at 1000 mA g -1The cycle stability test results under current density. It can be seen that after 500 cycles, the capacity retention rate reaches 92%, and the coulombic efficiency of each cycle is ~100%. This shows that the alloy material has excellent cycle stability and electrochemical performance.

[0119] Example 7

[0120] This embodiment provides a high-capacity alloy negative electrode material: Pb 44.5 Bi 55.5 (wt%) binary alloy material, the specific synthesis method is basically the same as the above method, first prepare Pb 44.5 Bi 55.5 (wt%) binary alloy powder, except the mass percentage of the metal required for the alloy and the heating temperature on the heating stirrer was 130 °C, the remaining steps were consistent with Example 1. Then, Pb 44.5 Bi 55.5 (wt%) binary alloy electrodes were assembled into sodium ion half-cells for electrochemical performance testing.

[0121] Fig.19 The prepared Pb 44.5 Bi 55.5 The X-ray diffraction results of the binary alloy powder show that the alloy material is composed of hexagonal Pb 7 Bi 3 The scanning electron microscope image of the alloy powder is as follows: Fig. 20 As shown, it can be seen that the alloy material is in a regular spherical shape, and the particle size is mainly distributed between 10-25 μm.

[0122] Fig.21 Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) shows a high conductivity at 0.1 mV s -1 The cyclic voltammetry curves of the first three cycles at the scan rate. As can be seen from the figure, there are 6 pairs of redox peaks, and the first three cycles of the curves have good overlap, indicating that the alloying and dealloying processes of the material are highly reversible.

[0123] Fig. 22 Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) at 50 mA g -1 The charge and discharge curves of the first three cycles at a current density of . It can be seen that the charge and discharge curves are consistent with the cyclic voltammetry curves. From the first cycle charge and discharge curves, it can be found that the initial discharge capacity is 494 mAh g -1 , charging capacity is 418.3 mAhg-1 , the first-cycle Coulomb efficiency is as high as 84.68%.

[0124] Fig.23 Pb 44.5 Bi 55.5 (wt%) binary alloy powder assembled sodium ion half-cell rate performance at different current densities. -1 The sodium ion half-cell of this embodiment is tested at a rate performance of 8000 mA g -1 At a high current density of 320 mAhg -1 capacity, and returns to 50mA g -1 After the current density reaches 2000, the specific capacity can still be recovered. It can be seen that the battery system has good rate performance and cycle stability.

[0125] Fig.24 Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) was tested at 1000 mA g -1 The cycle stability test results under current density. It can be seen that after 500 cycles, its capacity retention rate can still be as high as 93%, and the coulombic efficiency of each cycle is ~100%. This result further shows that Pb 44.5 Bi 55.5 (wt%) binary alloy materials have excellent cycling stability.

[0126] Comparative Example 2

[0127] The Pb in Example 7 44.5 Bi 55.5 The binary alloy powder (wt%) is replaced with a powder directly mixed with Pb and Bi powder in the same proportion as the negative electrode material of the sodium ion battery, and the rest remains unchanged, which is recorded as Pb 44.5 / Bi 55.5 The powders were mixed and then assembled into sodium ion half-cells for electrochemical performance testing. The specific method is as follows:

[0128] Preparation of Pb 44.5 / Bi 55.5 When mixing powders, if Pb in Example 7 44.5 Bi 55.5 The alloy powder, i.e. the active material, is weighed 80 mg. Similarly, the active material in the comparative example is also weighed 80 mg. Then the corresponding Pb powder (according to Pb 44.5 / Bi 55.5The mass of the Pb powder is 35.6 mg, and the mass of the Bi powder is 44.4 mg. Then the Pb powder and Bi powder are directly mixed to obtain Pb 44.5 / Bi 55.5 Mix the powder. 44.5 / Bi 55.5 Mixed powder was prepared into Pb 44.5 / Bi 55.5 The preparation, assembly and electrochemical performance testing methods of the mixed powder electrode and button cell are the same as those in Example 7.

[0129] Fig.25 Pb 44.5 / Bi 55.5 Mixed powder with Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) at 50 mA g -1 Comparison of charge and discharge curves under current density. It can be seen that Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from the binary alloy powder (wt%) has a slower charge and discharge platform and a relatively small polarization, indicating that the Pb 44.5 Bi 55.5 Binary alloy negative electrode materials can better exert the electrochemical properties of the alloy raw metals and have better electrochemical activity.

[0130] Fig.26 Pb 44.5 / Bi 55.5 Mixed powder with Pb 44.5 Bi 55.5 Comparison of the rate performance of sodium ion half-cells assembled from binary alloy powders at different current densities. -1 The rate performance test was carried out under 8 A g. -1 At a current density of 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powder (wt%) can still obtain 318 mAhg -1 The capacity of Pb 44.5 / Bi 55.5 The sodium ion half-cell assembled from the mixed powders was -1 At a current density of only 191 mAhg -1 This shows that Pb 44.5 Bi 55.5 (wt%) binary alloy materials have excellent rate performance. This is due to the fact that Pb44.5 Bi 55.5 (wt%) binary alloy materials have better metal synergy than single metals. Bi in the alloy reacts first, and the generated Na 3 Bi alloy deposition on the material surface provides fast ion transport channels and improves its kinetic properties.

[0131] Fig. 27 Pb 44.5 / Bi 55.5 Mixed powder with Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) was tested at 1000 mA g -1 Comparison of cycle stability test results under current density. As can be seen from the figure, after 500 cycles, Pb 44.5 Bi 55.5 The sodium ion half-cell assembled from binary alloy powders (wt%) can still obtain 363 mAh g -1 The capacity retention rate is as high as 93%, while Pb 44.5 / Bi 55.5 After 500 cycles, the reversible capacity of the sodium-ion half-cell assembled from the mixed powder was only 243 mAh g -1 The capacity retention rate is 71.34%. 44.5 Bi 55.5 (wt%) binary alloy materials have excellent cycling performance.

[0132] Example 8

[0133] Using Pb in Example 2 32 Bi 52.5 Sn 15.5 The electrode prepared from the ternary alloy powder is the negative electrode of the sodium ion battery. 3 V 2 (PO 4 ) 2 F 3 (abbreviated as NVPF) is the positive electrode of sodium ion battery, 1 mol / L NaPF 6 / diethylene glycol dimethyl ether as electrolyte, the positive electrode, separator, electrolyte, and negative electrode are stacked in order, and 60 μL of the above electrolyte is dripped on the separator between the positive and negative electrodes to make it completely infiltrated, and the battery is encapsulated to obtain NVPF / / Pb 32 Bi 52.5 Sn 15.5 Full battery.

[0134] The working principle of the full battery is as follows Fig.28As shown, the left side of the figure is the homemade NVPF positive electrode material, and the right side is the Pb 32 Bi 52.5 Sn 15.5 Schematic diagram of the electrode prepared by ternary alloy powder. When charging, sodium ions escape from the NVPF lattice and diffuse through the electrolyte to embed into the negative electrode to produce an alloying reaction with the ternary alloy negative electrode material. When discharging, sodium ions escape from the negative electrode and embed into the positive electrode through the electrolyte to form a full battery.

[0135] Fig.29 NVPF / / Pb 32 Bi 52.5 Sn 15.5 Full cell at 50 mA g -1 The first three cycles of charge and discharge curves under current density are shown in the figure. As can be seen from the figure, the first cycle charge capacity is 602.8 mAh g -1 , the discharge capacity is 530.9 mAh g -1 , the first-cycle Coulomb efficiency is 88.07%.

[0136] Fig.30 NVPF / / Pb 32 Bi 52.5 Sn 15.5 Full cell at 1000 mA g -1 The long cycle test results under current density are shown in the figure. It can be seen that at 1000 mA g -1 After 500 cycles at the same current density, 240.3 mAh g -1 The capacity retention rate is 85.6%. This shows that NVPF / / Pb 32 Bi 52.5 Sn 15.5 The full battery has excellent electrochemical performance. This is because the NVPF positive electrode and alloy negative electrode of the full battery have stable structures, and the alloy negative electrode has the characteristics of high capacity and multi-gradient, which promotes the rapid transmission of sodium ions and the rapid conduction of electrons, making the electrochemical reaction process highly reversible.

Claims

1. A sodium ion battery, characterized in that: It includes a sodium ion battery alloy electrode; the sodium ion battery alloy electrode is an integrated sodium ion battery alloy electrode or a sodium ion battery powder alloy electrode; The preparation method of the sodium ion battery integrated alloy electrode is as follows: the liquid alloy is evenly coated on the current collector, and after cooling and solidification, the sodium ion battery integrated alloy electrode is obtained; the weight percentage composition of the liquid alloy is Pb 32 Bi 52.5 Sn 15.5 , Pb 28 Bi 50 Sn 22 , Pb 14.8 Bi 59.4 Sn 25.8 , Pb 36 Bi 16 Sn 48 or Pb 44.5 Bi 55.5 The preparation method comprises the following steps: weighing pure Pb, pure Bi or pure Sn with a purity greater than 99.9% according to the target ratio, placing the mixture in a crucible and heating it in a smelting furnace, using an inert gas to protect the liquid surface during the smelting process, and stirring the mixture thoroughly and evenly after all the metals are melted to obtain a liquid alloy negative electrode material; casting the liquid alloy negative electrode material into a mold, and storing it in the form of an alloy ingot after cooling and solidification; heating and melting the alloy ingot to form a liquid alloy negative electrode material again; the current collector is one of copper foil, aluminum foil or stainless steel; The preparation method of the sodium ion battery powder alloy electrode is as follows: powder alloy, conductive agent and binder are uniformly mixed under the action of solvent, uniformly coated on the current collector, and dried to obtain the sodium ion battery powder alloy electrode; the weight percentage composition of the powder alloy is Pb 32 Bi 52.5 Sn 15.5 , Pb 28 Bi 50 Sn 22 , Pb 14.8 Bi 59.4 Sn 25.8 , Pb 36 Bi 16 Sn 48 or Pb 44.5 Bi 55.5 The preparation method comprises the following steps: weighing pure Pb, pure Bi or pure Sn with a purity greater than 99.9% according to the target ratio, placing the mixture in a crucible and heating and melting it in a melting furnace, using an inert gas to protect the liquid surface during the melting process, and after all the metals are melted, stirring them evenly to obtain a liquid alloy negative electrode material; casting the liquid alloy negative electrode material into a mold, and storing it in the form of an alloy ingot after cooling and solidification; heating and melting the alloy ingot, dispersing it in a liquid state, and drying it to obtain a powdered alloy negative electrode material.

2. The sodium ion battery according to claim 1, characterized in that In the method for preparing the sodium ion battery powder alloy electrode, the mass ratio of the powder alloy, the conductive agent and the binder is 8:1:

1.

3. The sodium ion battery according to claim 1, characterized in that: In the preparation method of the sodium ion battery powder alloy electrode, the current collector is one of copper foil, aluminum foil or stainless steel; the conductive agent is one of conductive carbon black, Ketjen black, acetylene black, activated carbon, porous carbon or natural graphite; the binder is one of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, polytetrafluoroethylene or polyacrylic acid; and the solvent is N-methylpyrrolidone or deionized water.